A Review of Dietary Intake during Postpartum Period - Jusoh, Nur Nabila; Tengku Ismail, Tengku Alina (IIUM Medical Journal Malaysia, 2022)
The postpartum period is a critical period for maternal and infant health. There is clear evidence showing the short- and long-term health benefits for women to adopt a healthy diet during this period. An unhealthy diet during this period can lead to cardiovascular disease and mental health problem among the mothers. Besides, optimal food consumption during postpartum is crucial to support the additional nutrient requirements for breastfeeding and to reduce postpartum weight retention. Lack of social support and some harmful traditional dietary practices are among the barriers which prevent postpartum women from consuming balanced and nutritious food. Therefore, there is a need for effective nutritional intervention to promote better health for the population. Furthermore, the intervention should be culturally sensitive to respect the local traditional dietary practices for better community acceptance.